Strongly Unforgeable Ring Signature Scheme from Lattices in the Standard Model - Geontae Noh; Ji Young Chun; Ik Rae Jeong (Journal of Applied Mathematics)
In a ring signature scheme, a user selects an arbitrary ring to be able to sign a message on behalf of the ring without revealing the signer’s identity. Whistle-blowers especially find this useful. To date, various ring signature schemes have been proposed, all considered to be secure as existentially unforgeable with respect to insider corruption; that is, an adversary who chooses ring-message pairs for which he requests signatures, corrupts honest users, and obtains their signing keys can not produce forgeries for new ring-message pairs. Lattice-based ring signature schemes offer lower computational overhead and security from quantum attacks. In this paper, we offer a lattice-based scheme. We begin by showing that the existing ring signature schemes are not sufficiently secure, because existential unforgeability still permits a signer to potentially produce a new signature on previously signed messages. Furthermore, we show that existing ring signature schemes from lattices are not even existentially unforgeable with respect to insider corruption. We then improve previous schemes by applying, for the first time, the concept of strong unforgeability with respect to insider corruption to a ring signature scheme in lattices. This offers more security than any previous ring signature scheme: adversaries cannot produce new signatures for any ring-message pair, including previously signed ring-message pairs.